Extraordinary cranial specialization in a new genus of extinct duck (Aves: Anseriformes) from Kauai, Hawaiian Islands - Iwaniuk, Andrew N.; Olson, Storrs L.; James, Helen F. (Zootaxa, 2009)
Talpanas lippa is described as a new genus and species of waterfowl from Kauai, Hawaiian Islands, that is unlike any other known member of the order. It is characterized by a short, stout tarsometatarsus and a braincase that is shallow and wide relative to its length with very small orbits. In comparison with extant species, the optic foramen of Talpanas is remarkably small whereas the maxillo-mandibular foramen, which is the exit point of the trigeminal nerve, is grossly enlarged. Relative to skull length and foramen magnum area, the maxillo-mandibular foramen is one order of magnitude larger in cross-sectional area than that of extant Anseriformes. We conclude that Talpanas had reduced visual abilities, as reflected externally by its small orbits and optic foramen, and a grossly hypertrophied trigeminal foramen. Taken together, this suggests that Talpanas may have been more heavily reliant upon somatosensory (tactile) cues for foraging than any living species of bird. Pectoral elements are unknown, but the evident lack of keen eyesight suggests that the species was flightless, as were many other insular waterfowl.